Institutional Performance and Utilization of Farm Machinery to Enhance Productivity and Income of Rice Farmers - Teguh Endaryanto; Sandi Asmara; Tanto Pratondo Utomo; Amanda Putra Seta; Firdasari Firdasari (The University of Lampung, 2025)
The utilization of technology in the agricultural industry is significantly growing recently. This is mostly due to its ability to enhance labor and land productivity, while simultaneously reducing production costs. The objective of this study is to examine the institutional performance and utilization of farm machinery (alsintan) by rice farmers, and to investigate the correlation between institutional performance and alsintan usage on the productivity and income of rice farmers. The study was carried out in two villages in the Central Lampung Regency, namely Rengas Village in Bekri District, and Trimurjo Village in Trimurjo District. Rice farmers in both villages actively utilized alsintan operated under the alsintan service unit (UPJA). The study findings indicate a strong and meaningful correlation between institutional performance and the utilization of alsintan with productivity and income level of tarmers. Alsintan technology directly impacted productivity and revenue with coefficients of 0.63 and 0.60, with confidence levels of 99.9% and 99.7%, respectively. Institutional performance indirectly affected them with a coefficient of 0.30 and a confidence level of 99.99%. The integration of enhancing institutional performance with the optimization of alsintan technology can foster the enhancement of other factors, such as human resource performance, group member involvement, and external environmental support. Keywords: Alsintan, Institutional, Optimization.